MiR-1270 Suppresses the Malignant Progression of Breast Cancer via Targeting MMD2. (19th March 2022) - Hu, Shaojun; Song, Yang; Zhou, Yu; Jiao, Yu; Wang, Song
Abstract : We aimed to detect the clinical significance of microRNA-1270 (miR-1270) in breast cancer (BCa) development and its potential influence on malignant phenotypes of BCa cells. The miR-1270 level in paired BCa and paracancerous tissues was detected. The Kaplan–Meier method was used for the prognosis analysis of miR-1270 in BCa. The biofunctions of miR-1270 in apoptosis and proliferation of breast cancer cells were evaluated. Downstream target of miR-1270 was predicted and confirmed. The involvement of monocyte to macrophage differentiation associated 2 (MMD2) in BCa development was finally illustrated. miR-1270 was lowly expressed in BCa tissues. Lowly expressed miR-1270 was associated with tumor staging, larger tumor size, and also worse prognostic results in patients with BCa. miR-1270 overexpression suppressed proliferation and increased apoptotic rate of BCa cells. Further exploration showed that MMD2 might be the target of miR-1270. MMD2 was upregulated in BCa tissues and negatively correlated to miR-1270 level. Importantly, MMD2 significantly neutralized the above biofunctions of miR-1270 in malignant phenotypes of BCa. Lowly expressed miR-1270 is a hallmark of poor prognosis in patients with BCa. It inhibits proliferative ability and increases apoptosis in BCa by negatively regulating the MMD2 level.